FDTB1, première étape du projet « French Discourse Treebank » : repérage des connecteurs de discours en corpus - Laurence Danlos; Margot Colinet; Jacques Steinlin (Discours)
This paper presents the identification of discourse connectives in the “French Treebank” corpus (FTB) already annotated for morpho-syntax. This is the first step in the full discursive annotation of this corpus. The method consists in projecting on the corpus the items that are listed in LexConn, a lexicon of French connectives, and then filtering the occurrences of these elements that do not have a discursive use, but for example are used as an adverb of manner or a preposition introducing a subcategorized complement. More than 10K connectives have been identified.